If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5y = 13 + -2x Solving 3x + -5y = 13 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 3x + 2x + -5y = 13 + -2x + 2x Combine like terms: 3x + 2x = 5x 5x + -5y = 13 + -2x + 2x Combine like terms: -2x + 2x = 0 5x + -5y = 13 + 0 5x + -5y = 13 Add '5y' to each side of the equation. 5x + -5y + 5y = 13 + 5y Combine like terms: -5y + 5y = 0 5x + 0 = 13 + 5y 5x = 13 + 5y Divide each side by '5'. x = 2.6 + y Simplifying x = 2.6 + y
| X=0.99X+310 | | 2x+(3+x)+x=27 | | 3x-5y=13+2x | | -2w-1+6w=1 | | 3x-5y=13+x | | -26c^2=36c | | X^2+y^2+6x+18y+90=60 | | 4x*110+5=180 | | 3+c=3 | | 35=(3w-8)w | | 2(8+3b)-(6-5b)=b+1-4b-5 | | X^2+y^2+6x+18x+90=60 | | 2(x+4)-3x=17 | | 18=0.5x(2+1) | | 2(x-4)-3x=17 | | 16=r(r-6) | | 414=24x | | 2u^2-u-1=(u-1)(u-1) | | 4x-15=12x+3 | | 5.7+6+4.3= | | 2u^2+5u+18=(u+4)(u+4) | | 6g+4(-4+5g)=1-8 | | x+6(-5x-8)= | | 0=2x^2-5x+19-(x-5)(x-5) | | 12x^2+1=8x | | 17x+51=6-4 | | 3x^2y+3xy^2-7x^2y+5xy^2= | | 25+0.45+m=40+0.25+m | | (3x-3y)dx+(3x-8y^3)dy=0 | | 12x^2y+13xy^2-2x^2y+15xy^2= | | 4x^2-48x-20y-16=0 | | 1(4)+4(5)=(1+4)c |